2019
DOI: 10.3390/cells9010014
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Expression Variability Implies Cell Function

Abstract: As single-cell RNA sequencing (scRNA-seq) data becomes widely available, cell-to-cell variability in gene expression, or single-cell expression variability (scEV), has been increasingly appreciated. However, it remains unclear whether this variability is functionally important and, if so, what are its implications for multi-cellular organisms. Here, we analyzed multiple scRNA-seq data sets from lymphoblastoid cell lines (LCLs), lung airway epithelial cells (LAECs), and dermal fibroblasts (DFs) and, for each ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 87 publications
4
27
0
Order By: Relevance
“…This happens even in a group of highly homogeneous cells of the same type. 12 The presence of so-called outlying cells, i.e., cells showing profiles of expression that deviate from those of most other cells, may influence the construction of high-precision scGRNs. Therefore, subsampling offers promise as a technique for handling the noise in the input datasets.…”
Section: Resultsmentioning
confidence: 99%
“…This happens even in a group of highly homogeneous cells of the same type. 12 The presence of so-called outlying cells, i.e., cells showing profiles of expression that deviate from those of most other cells, may influence the construction of high-precision scGRNs. Therefore, subsampling offers promise as a technique for handling the noise in the input datasets.…”
Section: Resultsmentioning
confidence: 99%
“…Key molecular determinants of cell-to-cell variability in B-cell fate decisions are NF-κB target genes. Indeed, recent single-cell RNA-sequencing analysis found that the most highly variable genes in lymphoid cells were functionally significant and centered around NF-κB and its target genes, including NFKBIA, MYC, IRF4, and AID ( Osorio et al, 2020 ).…”
Section: Putting the Pieces Togethermentioning
confidence: 99%
“…across samples) is often ignored and is generally only considered in terms of the impact it has on statistical power. However, gene expression variability has been shown to be under genetic control and important to cellular function [7][8][9][10][11]. Gene expression variability has been used to evaluate transcriptomic data in human disease and development [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%